Building climate resilience in small-scale aquatic food systems - Listman, George; Tigchelaar, Michelle; Majumdar, Rajita (WorldFish, 2025)
Locally led initiatives in Bangladesh, Timor-Leste, and Zambia show why small-scale fisheries and aquatic food producers need a seat at national climate change policy tables. Cases from three countries — Bangladesh, Timor-Leste, and Zambia — where small-scale fishers and aquatic food farmers are at the frontline of addressing climate change threats to their food security and livelihoods, illustrate ways in which local participation can contribute.